Design and performance characterization of H-band MCT camera: insights from pixel-level gain measurements - Qu, Wen-Qing; Wei, Jiang-Yuan; Ma, Hao-Ran; Ning, Yu; Li, Jia-Ming; Ge, Kun; Geng, Zhe; Zhang, Yu; Zhang, Hong-Fei; Wang, Jian (Frontiers in Astronomy and Space Sciences, 2025)
Infrared astronomical equipment is pivotal in advancing our understanding of the universe, particularly through ground-based observations, which remain the primary mode of astronomical study. In this paper, we introduce the development and performance characterization of an H-band Mercury Cadmium Telluride (MCT) infrared camera designed for astronomical observations. We computed the photon transfer curve (PTC) for each pixel and fitted these curves to derive pixel-level gain. The results reveal a spatial non-uniformity of detector pixel-level gain, which correlates with changes in field of view (FOV). By employing FOV compensation, we achieved more uniform gain distribution. This testing approach allows for a more accurate performance evaluation of scientific-grade astronomical cameras, providing a robust foundation for subsequent astronomical image analysis and benefiting the field of infrared astronomy.